Are food supply chains taking advantage of the circular economy? A research agenda on tackling food waste based on Industry 4.0 technologies - Lopes de Sousa Jabbour, Ana Beatriz; Frascareli, Fernanda Cortegoso de Oliveira [UNESP]; Santibanez Gonzalez, Ernesto D. R.; Chiappetta Jabbour, Charbel Jose (Taylor & Francis, 2021)
This article proposes a means of exploring the use of circular economy (CE) business models to deal with losses and waste in food supply chains. First, the current state-of-the-art application of CE in the food waste area was identified through a systematic literature review. The main findings concerning the current debate around this topic were: (a) the Regenerate and Loop business models are the most studied models in analyzing methods of reuse and recycling of food waste through biological cycles; (b) focal companies and customers are the most often investigated tiers of supply chains; and (c) the investigation of CE and food waste has so far focussed on how to efficiently manage the waste already generated by the system, instead of how to avoid waste generation. Second, in terms of managerial contributions, based on the findings from the systematic literature review, this article proposes an expansion of the application of CE business models to deal with food losses and waste, considering the role of the retail tier, the use of Industry 4.0 technologies and the shift away from the waste reuse approach towards reducing waste generation using CE business models, such as Optimize and Share. Additionally, in terms of academic contributions, this article presents a comprehensive agenda for future research and extends the body of knowledge with regard to the synergy between CE and Industry 4.0 by integrating these two topics with the issue of food waste and loss, a sustainable development target.
Keywords: Circular economy; closed-loop; food waste; Industry 4.0; ReSOLVE